When you look like us ebook - Harris, Pamela N. (2024)
“A high-speed story that will draw teens in and keep them turning pages until they reach the unpredictable and thrilling ending. A must for YA collections.”  (School Library Journal) A 2022 NAACP Image Award for Outstanding Literary Work nominee and a 2022 Edgar Award nominee, this timely, gripping teen novel is about a boy who must take up the search for his sister when she goes missing from a neighborhood where Black girls’ disappearances are too often overlooked, from debut author Pamela Harris. Perfect for fans of Jason Reynolds and Tiffany D. Jackson. When you look like us—brown skin, brown eyes, black braids or fades—everyone else thinks you’re trouble. No one even blinks twice over a missing Black girl from public housing because she must’ve brought whatever happened to her upon herself. I, Jay Murphy, can admit that, for a minute, I thought my sister Nicole just got caught up with her boyfriend—a drug dealer—and his friends. But she’s been gone too long. Nic, where are you? If I hadn’t hung up on her that night, she would be at our house, spending time with Grandma. If I was a better brother, she’d be finishing senior year instead of being another name on a missing persons list. It’s time to step up, to do what the Newport News police department won’t. Bring her home. Also a 2022 ALA Notable Book for a Global Society Award winner!